I bring you Good News of Great Joy for All the People (Hekima Review, 2010)
Let me begin by noting that this gospel passage takes our imagination to a near-drama point. Similarly, I will gear my following reflections towards a dramatization of a sort, but all along drawing on the imagination of Ignatius of Loyola